Handbook of Work-Family Integration: Research, Theory and Best Practices - Tremblay, Diane-Gabrielle (Relations industrielles / Industrial Relations, 2010)
The article reviews the book, "Handbook of Work-Family Integration: Research, Theory and Best Practices," edited by Karen Korabik, Donna S. Lero and Denise L. Whitehead.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z